Reliability of five methods for assessing shoulder range of motion - Hayes, K.; Walton, J.; Szomor, Z.; Murrell, G. A. (1999)
The comparable reliability of shoulder joint range of motion assessment tests, in symptomatic subjects, has yet to be established. An inter-rater and an intra-rater agreement trial was undertaken to establish the reliability of five different shoulder range of motion tests. These included visual estimation, goniometry, still photography, a tape measured distance of maximum overhead reach ("stand and reach") and a tape measured distance of maximum hand behind back reach. In the inter-rater trial, four examiners independently measured eight symptomatic subjects with the five range of motion tests for the movements of flexion, abduction, external rotation, hand behind back, "stand and reach" and hand behind back reach. In the intra-rater trial, a single examiner repeated the same assessment process with nine symptomatic subjects, on three different measurement occasions. Intra-class correlation coefficients (Rho) were derived by using a random effects model. For the inter-rater trial, the measurement of sagittal plane flexion was significantly more reliable than both abduction and external rotation for visual estimation (p=0.01, p=0.01), goniometry (p=0.01, p=0.002) and still photography (p=0.01, p=0.002). Hand behind back was consistently the least reliable movement. These results show that visual estimation was as reliable as the more complex methods for assessing shoulder range of motion.